MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI BERMAIN GELANG DIKELOMPOK B2 TK PEMBINA NEGERI 1 BANGKO BAGAN SIAPIAPI - Eliyusna Eliyusna; Zulkifli Zulkifli; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was conducted using games bracelets are useful as general information and the knowledge to know the epitome of the high numbers to determine the increase in capacity through bermainan bracelet in the 5-6 year age group B2 Nursery School 1 BangkoBagansiapiapi Trustees.Application of play bracelets to improve the ability to know the epitome of numbers grouped B2 executed in groups or with individuals but with the way alternately play activities jointly bracelet bracelet thrown into a pile and then calculate the bracelet that goes ketiang inserted into the box numbers in the first cycle, while in the second cycle of children throwing bracelet matches the color of the pole is then calculated and dimasuk into the box numbers.The ability to know the epitome of numbers through play bracelets of 92.80% with a very good criterion in Group B2 TK Pembina State 1 BangkoRokanHilir. The average value of 37.50% before the cycle and the first cycle increased by 50.00% and in the second cycle increased again with an average value of 72.30%. The percentage increase in the ability to know the symbol of B2 group numbers using the media bracelets in Group B2 country TK Pembina I BangkoBagansiapiapi from prior cycle to cycle II of 92.80%.Keywords :Coat Numbers , Playing Bracelet